Construction of a series of metal-directed MOFs to explore their physical and chemical properties. (24th March 2021) - Akhtar, Sohel; Singha, Pabitra; De, Avik; Das, Krishna Sundar; Saha, Sayan; Bala, Sukhen; Mondal, Raju
Abstract : Here, we report a series of metal-directed coordination polymers and explore their various properties. The polymeric networks show interesting properties such as selective CO2  gas adsorption, Fenton-type photocatalytic dye degradation and heterogeneous catalytic reduction of 4-nitrophenol. Abstract : In this manuscript, we describe the construction and self-assembly studies of a series of metal-directed coordination polymers using a combination of dicarboxylic acid, 5-azido isophthalic acid (N3 -IPA) and bipyridine, 1, 2-bis(4-pyridyl)-ethane (BPE) mixed-ligand systems. The combination of a rigid acid and a flexible bipyridyl ligand serves the purpose of generating diverse architectures with different metal centres ranging from two-dimensional grids and complex three-dimensional frameworks. The ligand molecules exhibited variable conformations as well as variable coordination behaviours when different metal ions were used. We report herein, the synthesis and structural aspects of seven metal-directed MOFs, {[Cu(μ-N3 -IPA)(μ-BPE)]·(DMF)0.5 } n (1 ), [Co(μ-N3 -IPA)(μ-BPE)1.5 ] n (2 ), [Ni(μ-N3 -IPA)(μ-BPE)1.5 ] n (3 ), [Cd(μ-N3 -IPA) (N3 -HIPA) (μ-BPE)] n (4 ), {[Mn(μ-N3 -IPA)(μ-BPE)1.5 ]·(DMF)(H2 O)} n (5 ), {[Zn(μ-N3 -IPA)(μ-BPE)]·[(H2 O)](CH3 OH)} n (6 ), [Zn(μ-N3 -IPA)(μ-BPE)] n (7 ). Compounds 1 and 3 showed interesting structures, wherein the immobilized nitrogen-rich azide groups are situated in the inner surfaces of the walls that encompass a columnar pore, which represents a highly favourable situation for the CO2 gas adsorption. Both compounds showed the selective uptake of CO2 gas compared to N2 gas. The cobalt-based compound 2 showed an impressive photocatalytic degradation of toxic dye molecules with a potential application in environmental remediation. The copper-based compound 1, on the other hand, exhibited a nice example of a heterogeneous catalytic reduction of 4-nitrophenol to 4-aminophenol.